Persistent SARS‐CoV‐2 infection in patients seemingly recovered from COVID‐19. Issue 3 (18th January 2023) - Bussani, Rossana; Zentilin, Lorena; Correa, Ricardo; Colliva, Andrea; Silvestri, Furio; Zacchigna, Serena; Collesi, Chiara; Giacca, Mauro
Abstract: SARS‐CoV‐2 infection is clinically heterogeneous, ranging from asymptomatic to deadly. A few patients with COVID‐19 appear to recover from acute viral infection but nevertheless progress in their disease and eventually die, despite persistent negativity at molecular tests for SARS‐CoV‐2 RNA. Here, we performed post‐mortem analyses in 27 consecutive patients who had apparently recovered from COVID‐19 but had progressively worsened in their clinical conditions despite repeated viral negativity in nasopharyngeal swabs or bronchioalveolar lavage for 11–300 consecutive days (average: 105.5 days). Three of these patients remained PCR‐negative for over 9 months. Post‐mortem analysis revealed evidence of diffuse or focal interstitial pneumonia in 23/27 (81%) patients, accompanied by extensive fibrotic substitution in 13 cases (47%). Despite apparent virological remission, lung pathology was similar to that observed in acute COVID‐19 individuals, including micro‐ and macro‐vascular thrombosis (67% of cases), vasculitis (24%), squamous metaplasia of the respiratory epithelium (30%), frequent cytological abnormalities and syncytia (67%), and the presence of dysmorphic features in the bronchial cartilage (44%). Consistent with molecular test negativity, SARS‐CoV‐2 antigens were not detected in the respiratory epithelium. In contrast, antibodies against both spike and nucleocapsid revealed the frequent (70%) infection of bronchial cartilage chondrocytes and para‐bronchial gland epithelial cells. In a few patients (19%), we also detected positivity in vascular pericytes and endothelial cells. Quantitative RT‐PCR amplification in tissue lysates confirmed the presence of viral RNA. Together, these findings indicate that SARS‐CoV‐2 infection can persist significantly longer than suggested by standard PCR‐negative tests, with specific infection of specific cell types in the lung. Whether these persistently infected cells also play a pathogenic role in long COVID remains to be addressed. © 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.